The Ideal Prison Officer Reconsidered: Between Institutional Expectations and Everyday Practice - Vaičiūnienė, Rūta; Dainauskaitė, Goda (Kriminologijos studijos, 2024)
The article examines the role of prison officers in contemporary penal systems, with particular attention to the distribution of power, the influence of managerial governance, and the duality of officers’ professional functions. Drawing on theoretical and empirical research (Bennett, 2024; Crewe, 2011; Liebling & Crewe, 2013), it analyses how a shifting approach to imprisonment, centred on “soft power,” standardised procedures, and bureaucratic mechanisms, transforms the everyday practices of prison staff. The article explores the challenges emerging in the Lithuanian prison system within the context of managerial reforms, where local traditions interact with global governance models, producing a unique, hybrid penal reality. Based on a qualitative study involving Lithuanian prison staff (including contact officers, policymakers, and trade union representatives), the article reveals a fundamental gap between the declared goals of penal system reforms and the lived realities of prison life. On the one hand, the Lithuanian prison system is moving toward Western standards, emphasising social reintegration and introducing managerial principles. On the other hand, deeper staff cultures and practices are changing more slowly, with employees perceiving the reforms as largely declarative and challenging to implement in practice. Contact officers involved in the study feel like hostages of the system, bound by formal procedures rather than being able to build relationships with prisoners that they prioritise. The findings indicate that meaningful progress requires actively including staff in the reform process: addressing their material and emotional needs and creating conditions that allow them to perform their evolving functions effectively.
Keywords: prison staff; prison governance; managerialism; “soft power”; former Soviet Union countries; Lithuania